2021
DOI: 10.1111/phpp.12755
|View full text |Cite
|
Sign up to set email alerts
|

Sun exposure and protection habits in transplant athletes: An international survey

Abstract: Background Transplant recipients are particularly prone to the development of skin cancer, and overexposure to UV radiation during outdoor activities increases the risk of carcinogenesis. Objective The aim of this study was to analyze sun‐related behaviors and knowledge in transplant athletes, examine the frequency of sunburns, and explore associations with a history of skin cancer. Materials and methods Cross‐sectional descriptive study. Participants (n = 170) in the XXI World Transplant Games from >50 countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…These incidents were significantly more common in younger transplant athletes. Moreover, lower education status correlated with more sunburns [ 47 ]. The study revealed a relatively high awareness of photoprotection in transplant athletes.…”
Section: Resultsmentioning
confidence: 99%
“…These incidents were significantly more common in younger transplant athletes. Moreover, lower education status correlated with more sunburns [ 47 ]. The study revealed a relatively high awareness of photoprotection in transplant athletes.…”
Section: Resultsmentioning
confidence: 99%